1975
DOI: 10.1007/bf00484917
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly labeled proteins on the salivary gland chromosomes of Drosophila melanogaster

Abstract: Experiments on short-term and pulse-chase labeling of chromosome proteins of the salivary glands of Drosophila melanogaster show unique patterns of label in the vicinity of chromosome puffs. A high turnover rate is indicated for these nonhistone proteins, which appear to form a fibrous sheath around the chromosomes. Acrylamide gel analyses of the chromosomal proteins that are quickly labeled, comparing compositions at different stages of development with compositions after heat shock, show that all are differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…Furthermore, evidence of control of protein synthesis at the transcriptional level was also presented. By pulse-labeling of salivary gland proteins, Mitchell and Lipps [9] confirmed the conclusion of Berendes [3] that protein accumulation precedes RNA synthesis at a puff site. Specifically, at 0 h prepupae pulse-labeled salivary gland showed an accumulation of label at 85D just about an hour before it is due to puff.…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, evidence of control of protein synthesis at the transcriptional level was also presented. By pulse-labeling of salivary gland proteins, Mitchell and Lipps [9] confirmed the conclusion of Berendes [3] that protein accumulation precedes RNA synthesis at a puff site. Specifically, at 0 h prepupae pulse-labeled salivary gland showed an accumulation of label at 85D just about an hour before it is due to puff.…”
Section: Introductionmentioning
confidence: 68%
“…Previous reports have indicated that Drosophila heat-shock proteins are transported into the nucleus soon after synthesis (16,31). Vincent and Tanguay (32) have also shown in Chironomous tentans by microdissection that some heatshock proteins exhibit a broad intranuclear distribution.…”
Section: Discussionmentioning
confidence: 92%
“…Samples for observing bristle morphology were prepared as described by Mitchell and Lipps [l] , and those for observing chromosome autoradiographs were made as described earlier [ 1,9] .…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…These various facts show different kinds of correlations between the presence of heat-shock proteins and protection phenomena. They suggest but do not prove that the heat-shock protein(s) is directly involved physically with the storage of mRNA and/or the regulation of protein synthesis just as they have been shown to be involved directly with salivary gland chromosomes [9]. There now seems little doubt that heat shock does affect storage of the message and preferential translation of the message after heat shock is well established [12,13,141.…”
Section: Protein Synthesis and Protection For Survivalmentioning
confidence: 99%
See 1 more Smart Citation